Biostratigraphic Analysis of Middle to Late Eocene Palynomorphs from The Upper Gercus Formation, Dohuk Area, Northern Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
The current study focuses on the palynological study of the upper part of the Gercus Formation of (Middle to Late Eocene) age in northern Iraq. Fifteen samples were collected from the studied outcrops. The studied section is about 57 meters. Twelve species belonging to eleven genera of spores and pollen grains are identified as follows: Sphagnum triangularum, Polypodiaciesporites retirugatus, Verrucatosporites usmensis, Monoporites annulatus, Perfotricolpites nigerianus, Tricolpites cf. brevicolpus, Retitricolporites irregularis, Psilatricolporites crassus, Psilatricolporites cryptoporus, Gemmastephanocolporites brevicolpites, Pinus sp, Cycas sp.  Based on the stratigraphic distribution of the identified palynomorph species, three palynological zones have been recognized, arranged in ascending order from the lowest (oldest) to the uppermost (youngest) part of the section as follows:1- Monoporites annulatus - Gemmastephanocolporites brevicolpites interval Biozone (M1)2- Gemmastephanocolporites brevicolpites Range Biozone (M2)3- Perfotricolpites nigerianus Range Biozone (L)These biozone are correlated and compared with other studies outside Iraq. The biostratigraphic analysis conducted in the present study indicates that the Gercus Formation is of Middle to early Late Eocene age.
Keywords: Midle - late Eocene, reworked Spores – Pollen, Gercus Formtion,